Infrastructure in Philippine development - Cayetano W. Paderanga (University of the Philippines, School of Economics (UPSE), 2007)
Studies linking infrastructure and development support the idea that there are large returns to infrastructure investments. This paper examines the conceptual bases for infrastructure's role and their implementation in the Philippines. Regressions show that capital stock investments have yielded insignificant effects on Philippine output from 1955-2001. A survey of different sectors suggests that poor government management has severely limited the effectiveness of resource mobilization and reduced the rate of return on infrastructure investments in the country. Recent experience indicates that allowing greater private sector involvement may address pressing issues regarding efficiency in provision and funding capabilities until the government develops the ability for effective resource mobilization. It is recommended that the government focus on strengthening future financing capacity to meet expected increases in demand for infrastructure services. Caution, however, must be exercised in the overly liberal provision of performance guarantees as this may lead to significant government expenditure increases in the future.
Keywords: 330; Infrastrukturinvestition; Entwicklung; Philippinen